Merriam -Webster's concise dictionary of English usage - Websters, Merriam (Massachusetts Merriam Webster's Incorporated, 2002)
Merriam-Webster's ConciseDictionary of English Usage A handy guide to problems of confused and disputed usageAre you anxious or eager to settle these disputes?If you affect something, is the result an effect?Is alRight all Right?Does less of an amount result infewer innumber?Do you take a glance and get a glimpse?More than 2,000 comprehensive articles explore the historical background and present-day usage trends of commonly confused and disputed words and phrases. Articles include expert analysis, discussion of alternatives and practical advice. Thousands of quotations from a wide variety of sources illustrate patterns of established usage.
Keywords: English Dictionary